Health Workers' Performance in the Midst of the Covid-19 Pandemic - Athoillah Athoillah; Desti Ranihusna; Erianto Hasibuan; Angga Arizky Lindu Aji Pratama (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2022)
This study examines the effect of work-life balance, occupational health and safety, and job satisfaction on performance in three public health centers in Semarang Regency. The type used in this research is quantitative research. The method used in this study is the SEM-PLS method and the SmartPLS analytical software which includes a questionnaire with 114 samples. The research instrument is part of the SEM-PLS method and SmartPLS software. The research findings indicate that while the relationship of work-life balance on performance may be mediated by job satisfaction, the relationship of occupational health and safety on performance cannot. As a result, work-life balance and occupational health and safety both have an indirect impact on performance.